Fatigue in the chronic fatigue syndrome: a cognitive phenomenon? - Fry, A; Martin, M (1996)
What is the source of the perception of excessive fatigue in the chronic fatigue syndrome (CFS)? Studies of physiological response to aerobic activity, of muscle pathology and muscle function in CFS, are reviewed, and suggest that the subjective report of fatigue is not due to any peripheral impairment. In addition, current technological methods such as electroencephalography have failed to uncover the nature of any abnormality in the central motor unit. A physiological model which proposes that patients with CFS possess a reduced threshold for sensory fatigue signals is rejected, because it fails to account for recent findings. Instead, it is suggested that the perception of fatigue in CFS is enhanced by idiosyncrasies in cognitive processing. The implications of this view to our understanding of the perpetuation of CFS as a whole are explored.